Prediction of Alzheimer's disease diagnosis within 14 years through Aβ misfolding in blood plasma compared to APOE4 status, and other risk factors. Issue 2 (6th January 2020) - Stocker, Hannah; Nabers, Andreas; Perna, Laura; Möllers, Tobias; Rujescu, Dan; Hartmann, Annette; Holleczek, Bernd; Schöttker, Ben; Gerwert, Klaus; Brenner, Hermann
Abstract: Introduction: Alzheimer's disease (AD) has a long prodromal stage and identifying high‐risk individuals is critical. We aimed to investigate the ability of Aβ misfolding in blood plasma, APOE4 status, and dementia risk factors to predict diagnosis of AD. Methods: Within a community‐based cohort, Aβ misfolding in plasma measured by immuno‐infrared sensor and APOE genotype were determined at baseline in 770 participants followed over 14 years. Associations between Aβ misfolding, APOE4, and other predictors with clinical AD, vascular dementia, and mixed dementia diagnoses were assessed. Results: Aβ misfolding was associated with a 23‐fold increased odds of clinical AD diagnosis within 14 years. No association was observed with vascular dementia/mixed dementia diagnoses. APOE4 ‐positive participants had a 2.4‐fold increased odds of clinical AD diagnosis within 14 years. Discussion: Aβ misfolding in blood plasma was a strong, specific risk prediction marker for clinical AD even many years before diagnosis in a community‐based setting.